Genotypic variation for phytic acid, inorganic phosphate and mineral contents in advanced breeding lines of wheat (Triticum aestivum L.) - A.S. Shitre, D.A. Gadekar1, V. Ramachandran, Vikas, S. Bakshi, V. Kumar, G. Vishwakarma and B.K. Das (Electronic Journal of Plant Breeding, 2015)
Wheat is a staple food of Indian population. Its nutritional and quality parameters have gained considerable importance over past few decades. In the present study, genotypic variation was studied in 100 advanced breeding lines developed for Indian peninsular zone by measuring phytic acid (PA), inorganic phosphate (IP), iron and zinc content in seeds and hundred kernel weight (HKW). Advanced breeding lines under investigation exhibited wide variation for the characters studied. The PA content ranged from 4.97 mg/g to 15.02 mg/g (mean of 9.58 mg/g). Iron and zinc content was in the range of 0.042 to 0.098 mg/g and 0.017 mg/g to 0.029 mg/g respectively. HKW ranged from 2.99 to 5.42 g. There was significant negative correlation between PA and HKW. Iron content showed very high genotypic coefficient of variation and heritability (h2bs) as compared to zinc content and other traits. Low heritability of IP content indicated the environmental influence on the trait.